Strategi Pengembangan Merek Untuk Batik Tulis Asthina Melalui Pemasaran Digital - Cicih Maryati; Dini Selasi; Putri Meylani; Nur Azijah; Nur Faadhilah (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
In an increasingly digital era, traditional marketing must be equipped with digital strategies to compete in the global market. The purpose of this study is. develop an effective digital distribution strategy to increase brand awareness and sales of Batik Tulis Asthina. The research method used is a case study with a qualitative approach. Information was also obtained from interviews with the owners. The results show that the use of Tokopedia's social media such as Instagram, Facebook, and Shopee significantly increases brand visibility and interaction with customer